القضاء و الإفتاء الحنفي في تونس خلال العهد العثماني 1574م1881م - شايب ذكرى (My University, 2025)
Abstract: This study includes the transformation that occurred in the province of Tunisia during the Ottoman era, especially in the judicial field and fatwas by adopting the Hanafi school of thought as the official school of thought of the state, which returned to spread with the arrival of the Ottomans despite the continued dominance of the Maliki school of thought within Tunisian society. It also focuses on the most important changes that occurred in the Hanafi judiciary and fatwa plans through the appointment and creation of new judicial positions and ranks, especially in The period of rule of the Muradids and Husseinis, which was assumed by several Maliki and Hanafi sheikhs and scholars This indicates the harmony of the two schools of thought, and it also aims to identify the most important Hanafi religious educational institutions in Tunisia, represented by mosques and schools that teach Hanafi jurisprudence and work to spread its teachings. ------------------------ الملخص: تضم هذه الدراسة التحول الذي طرأ على إيالة تونس خلال العهد العثماني لاسيما في المجال القضائي و الإفتائي من خلال اعتماد المذهب الحنفي كمذهب رسمي للدولة و الذي عاد للانتشار بمجيئ العثمانيين رغم استمرار هيمنة المذهب المالكي داخل المجتمع التونسي ، كما أنها تركز على أهم التغييرات التي طرأت على خطتي القضاء و الإفتاء الحنفية من خلال تعيين و استحداث مناصب و رتب قضائية جديدة خاصو في فترة حكم المراديين و الحسينيين و التي تولاها عدة شيوخ و علماء مالكيين و أحناف ، وهذا ما يدل على انسجام المذهبين ، كما أنها تهدف الى التعرف على أهم المؤسسات الدينية التعليمية الحنفية في تونس المتمثلة في الجوامع و المدارس التي تدرس الفقه الحنفي و تعمل على نشر تعاليمه . -------------------------------- Résumé : La présente étude met en évidence les transformations qu’a connues la Régence de Tunis durant la période ottomane, en particulier dans les domaines judiciaire et religieux. Elle s’intéresse notamment à l’adoption du rite hanafite en tant que doctrine officielle de l’État, qui a regagné en influence avec l’arrivée des Ottomans, malgré la persistance de la prédominance du rite malékite au sein de la société tunisienne. L’analyse porte sur les mutations majeures affectant les fonctions judiciaires et muftiates de tradition hanafite, à travers la nomination et la création de nouveaux postes et grades juridiques, notamment sous les dynasties mouradite et husaynite. Ces fonctions furent assurées par des savants et cheikhs issus tant de l’école malékite que de l’école hanafite, témoignant ainsi d’une forme de cohabitation doctrinale harmonieuse. L’étude vise également à recenser les principales institutions religieuses et éducatives de rite hanafites.
Keywords: القضاء، الإفتاء الحنفي، تونس، العهد العثماني 1574م1881م